PROSES BERPIKIR KRITIS SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA REALISTIK MATERI GEOMETRI DITINJAU DARI GAYA BELAJAR - Finsensius Yesekiel Naja; Agustina Mei; Sofia Sa'o (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2020)
The purpose of this study is to describe the profile of students' critical thinking in solving realistic mathematical problems of geometry material in terms of learning styles. This research is a descriptive study with a qualitative approach. Critical thinking in this study refers to critical thinking with FRISCO criteria. In this study, subjects were taken from students of class VII SMP N 2 Ende Selatan. Each student's research subjects have visual, auditory, and kinesthetic learning styles. Data collection is done by providing a Problem Solving Test (TPM) and an interview. The results obtained, subjects who have a visual learning style, critical thinking processes in solving realistic mathematical problems, able to understand problems, the subject has not been able to determine ways to solve problems, the subject has not been able to carry out the settlement and the subject does not re-examine. Subjects who have auditory learning styles, critical thinking profiles in solving realistic mathematical problems are able to understand problems, but the subject does not re-examine. Subjects who have kinesthetic learning styles of critical thinking processes in solving realistic mathematical problems are able to understand problems, are able to plan problems, subjects can carry out well and check the results.